Association between change in self-reported sugar intake and a sugar biomarker (δ13C) in children at increased risk for type 1 diabetes. (2020) - Henze, Martha M.; Bemis, Elizabeth A.; Seifert, Jennifer A.; Johnson, Randi K.; Dong, Fran; Rewers, Marian; Norris, Jill M.
Abstract: We examined whether change in added sugar intake is associated with change in δ 13 C, a novel sugar biomarker, in thirty-nine children aged 5–10 years selected from a Colorado (USA) prospective cohort of children at increased risk for type 1 diabetes. Reported added sugar intake via FFQ and δ 13 C in erythrocytes were measured at two time points a median of 2 years apart. Change in added sugar intake was associated with change in the δ 13 C biomarker, where for every 1-g increase in added sugar intake between the two time points, there was an increase in δ 13 C of 0⋅0082 ( P = 0⋅0053), independent of change in HbA1c and δ 15 N. The δ 13 C biomarker may be used as a measure of compliance in an intervention study of children under the age of 10 years who are at increased risk for type 1 diabetes, in which the goal was to reduce dietary sugar intake.